Trophic biology of the twospot livebearer, Pseudoxiphophorus bimaculatus, an invasive fish in Teuchitlán River, central Mexico - Valentin Mar-Silva; Martina Medina-Nava; Yvonne Herrerías-Diego; Juan P. Ramírez-Herrejón; Omar Domínguez-Domínguez (Revista Mexicana de Biodiversidad)
The Teuchitlán River in Mexico is a hotspot of fish diversity, with 3 endemic species. Pseudoxiphophorus bimaculatus has been introduced into the river, but its trophic impact on the system is unknown. We determined the importance of each food item in the diet of P. bimaculatus with a relative importance index, their feeding behavior using an omnivorous index, the trophic position with the TrophLab program, and the niche breadth using the standardized Levin index. We performed Permanova analyses to compare diet between size classes, sites, and seasons. We analyzed 631 P. bimaculatus individuals. The species consumed mainly terrestrial insects, but presented an herbivorous trend in some sites. A generalist trophic behavior was presented in the wet season and a specialist behavior in the dry season occupying different trophic levels and presenting variable trophic width. This flexible feeding strategy enables P. bimaculatus to exploit resources from different trophic levels. The high consumption (%RII > 50) of terrestrial insects could indicate that P. bimaculatus may transport allochthonous energy into the river. Furthermore, the high invasive potential of the species represents a risk for the freshwater ecosystems of central Mexico, a region that has been recognized as a hotspot for freshwater fish conservation.